2004
DOI: 10.1111/j.1399-5618.2004.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder in patients with bipolar disorder: a review of prevalence, correlates, and treatment strategies

Abstract: These findings are discussed in relation to the cost of PTSD symptoms to the course of bipolar disorder. Pharmacological and cognitive-behavioral treatment options are reviewed, with discussion of modifications to current cognitive-behavioral protocols for addressing PTSD in individuals at risk for mood episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 106 publications
(142 reference statements)
5
91
2
3
Order By: Relevance
“…[35,36] Bipolar bozukluk olgularında yaşam boyu TTSB yaygınlığının %16-39 oranında olduğu düşünülmektedir. [37] TSSB eş tanısı kadınlarda erkeklerden 2 kat daha fazla görülür. [38] Bunların yanı sıra manik ve hipomanik ataklarda deneyimlenen travmatik olayların travma belirtilerini bastırabileceği ileri sürülmektedir.…”
Section: Psikiyatrik Bozukluklarunclassified
“…[35,36] Bipolar bozukluk olgularında yaşam boyu TTSB yaygınlığının %16-39 oranında olduğu düşünülmektedir. [37] TSSB eş tanısı kadınlarda erkeklerden 2 kat daha fazla görülür. [38] Bunların yanı sıra manik ve hipomanik ataklarda deneyimlenen travmatik olayların travma belirtilerini bastırabileceği ileri sürülmektedir.…”
Section: Psikiyatrik Bozukluklarunclassified
“…This may be due to disruptive behavior during mania or to increased childhood trauma history. [81][82][83] As a result, BD patients usually report high rates of lifetime PTSD ranging from 16% to 39% in BD-I patients evaluated in the National Comorbidity Survey-Replication 84,85 Moreover, if the traumatic event occurs during manic or hypomanic phases, there is a higher probability of PTSD symptoms developing afterwards. 86 Recent studies suggested that a history of trauma may be related to BD's etiology and prognosis.…”
Section: 61mentioning
confidence: 99%
“…86 Recent studies suggested that a history of trauma may be related to BD's etiology and prognosis. 84 For example, early parental loss has been identified as a risk factor for BD. 87 Highimpact trauma has been associated with poor BD prognosis.…”
Section: 61mentioning
confidence: 99%
“…Among bipolar patients, rates of comorbid posttraumatic stress disorder (PTSD) and suicidal attempts were reported as 16.0% and 25-50%, respectively (1,2). It has been shown that the adults with bipolar disorder (BD) have an increased rate of sexual or physical abuse history at earlier ages which is known to be associated with greater prevalence of rapid cycling, suicidal attempts, co-morbid anxiety disorders, PTSD, substance use disorders, and personality disorders (3).…”
Section: Introductionmentioning
confidence: 99%